Predictive value of coaches` early technical and tactical notational analyses on long-term success of female handball players - Schorer, J.; Faber, I.; Koopmann, T.; Büsch, D.; Baker, J. (Journal of Sports Sciences, 2020)
Despite the importance of technique and tactics for athlete performance, there has been surprisingly little research on the value of these skills in talent identification and development. This study investigated the relationship between coaches` early notational analyses of female youth handball players and the long-term success of these athletes. Participants included sixty-eight female handball players involved in a talent selection camp in Germany when they were between 12 and 14 years of age (mean = 14.42, SD = 0.42). All subsequently ended up as non-, semi- or professional adult players. During the initial selection camp, participants were evaluated on a range of quantitative and qualitative measures of technical and tactical skill. Results indicated significant differences between the groups, but only for the number of actions taken, not for the quality of those actions. While this seems counterintuitive, it may reflect the likelihood that more skilled and/or talented players take more actions. Further work is necessary to explore the validity and implications of these findings.